1985
DOI: 10.1159/000261734
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Adjustments in Aspirated and Unaspirated Stops in Danish

Abstract: Vocal fold adjustments in Danish aspirated and unaspirated stops were investigated by electromyography, photo-electric glottography, and fiberoptic stills. The results show that these two stop types are produced primarily by different types of glottal gesture, rather than by a different timing of the glottal and supraglottal articulations. Other, more general aspects of glottal behaviour in relation to aspiration and devoicing in stops are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 6 publications
5
36
0
Order By: Relevance
“…Roux [1990] and Lewis [1998] also found that closure duration is shorter in aspirated plosives than in the other plosive types. This result is comparable to the aspiration and closure durations presented by Hutters [1985] for Danish. Hutters [1985] points out that one way of creating the long aspiration durations characteristic of Danish compared to other languages is by decreasing closure duration.…”
Section: Aspirationsupporting
confidence: 87%
See 3 more Smart Citations
“…Roux [1990] and Lewis [1998] also found that closure duration is shorter in aspirated plosives than in the other plosive types. This result is comparable to the aspiration and closure durations presented by Hutters [1985] for Danish. Hutters [1985] points out that one way of creating the long aspiration durations characteristic of Danish compared to other languages is by decreasing closure duration.…”
Section: Aspirationsupporting
confidence: 87%
“…This result is comparable to the aspiration and closure durations presented by Hutters [1985] for Danish. Hutters [1985] points out that one way of creating the long aspiration durations characteristic of Danish compared to other languages is by decreasing closure duration. Related proposals about negative correlations between closure and aspiration duration are made by Kohler [1984], Docherty [1992], and Maddieson [1997].…”
Section: Aspirationsupporting
confidence: 87%
See 2 more Smart Citations
“…VOT is a reliable cue to distinguish between voiced and voiceless stops in English, as well as a number of other languages [3][4][5] . As an acoustic cue, VOT also serves as an inferential estimate of speech motor control, requiring fi ne motor coordination of the respiratory, phonatory, and articulatory structures [6] .…”
Section: Introductionmentioning
confidence: 99%